THE ROLE OF ELEMENTARY SCHOOL TEACHERS IN PREPARING THE GOLDEN GENERATION THROUGH THE PANCASILA STUDENT PROFILE - Elinda Rizkasari (EDUPEDIA, 2022)
Education is the key to changing the world, through improving the quality of education, it is hoped that Indonesia will be able to produce a golden generation of superior character. As an effort to welcome the golden generation that is strong and has good morals, the role of teachers at the elementary school level is very crucial. As an educator for the prospective golden generation, it takes the best possible effort to prepare a golden generation who has 21st-century skills with superior character, critical thinking, creativity, innovation, communication, collaboration, and competition. The research was conducted using the library research method. One of the government's efforts to prepare the golden generation is by "boiling" and improving the quality in the field of education, including by improving the curriculum and increasing teacher competence which is currently still ongoing. The role of the teacher to succeed in implementing the Pancasila student profile requires optimal efforts. One form of effort to strengthen the ability of educators to carry out projects to strengthen the profile of Pancasila students is to be carried out independently by the Education unit or in collaboration with Education partners for capacity building both offline and online. The development is carried out in a series and sustainable manner by the learning needs of educators, this development can be carried out through training, discussion of literature review, and various good practices in the learning community.